COVID-19 Vaccines in the Pediatric Population: A Focus on Cardiac Patients - Ghena Lababidi; Hossam Lababidi; Fadi Bitar; Mariam Arabi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Due to the deleterious global impact of the COVID-19 pandemic, tremendous effort has been invested in the development of vaccines against the virus. Vaccine candidates are first tested in adult populations, a number of which have been approved for EUL by the WHO, and are in use across the USA and MENA region. The question remains whether these (or other) vaccines should be recommended to a neonatal, pediatric, and/or adolescent cohort. Incidence and severity of COVID-19 infection are low in pediatric, neonatal, and adolescent patients. Since both overall incidence and severity are lower in children than in adults, safety is an important consideration in vaccine approval for these age groups, in addition to efficacy and a decreased risk of transmission. The following review discusses vaccine immunology in children aged 0–18 years, with emphasis on the negative impact of the COVID-19 pandemic on the lives of children, considerations for pediatric vaccine approval, and available vaccines for pediatric cohorts along with a breakdown of the efficacy, advantages, and disadvantages for each. This review also contains current and future perspectives, as well as a section on the cardiovascular implications and related dynamics of pediatric COVID-19 vaccination.